Low-intensity focused ultrasound targeting the nucleus accumbens as a potential treatment for substance use disorder: safety and feasibility clinical trial - Mahoney, James J.; Haut, Marc W.; Carpenter, Jeffrey; Ranjan, Manish; Thompson-Lake, Daisy G. Y.; Marton, Jennifer L.; Zheng, Wanhong; Berry, James H.; Tirumalai, Padma; Mears, Ashley; D’Haese, Pierre; Finomore, Victor S.; et al. (Frontiers in Psychiatry, 2023)
This study evaluated two doses (60 and 90 watts) of Low Intensity Focused Ultrasound (LIFU), targeting the bilateral Nucleus Accumbens (NAc), in individuals with substance use disorder. Outcomes were the safety, tolerability, and feasibility during the LIFU procedure and throughout the 90-day follow-up. Outcomes also included the impact of LIFU on cue-induced substance craving, assessed via Visual Analog Scale (VAS), both acutely (pre-, during and post-procedure) and during the 90-day follow-up. Daily craving ratings (without cues) were also obtained for one-week prior to and one-week following LIFU. Four participants (three male), who were receiving comprehensive outpatient treatment for opioid use disorder at the time of enrollment and who also had a history of excessive non-opioid substance use, completed this pilot study. After confirming eligibility, these participants received 10 minutes sham LIFU followed by 20 minutes active LIFU (10 minutes to left then right NAc). Both LIFU doses were safe and well-tolerated based on reported adverse events and MRI scans revealed no structural changes (0 mins, 24 hour, and 1-week post-procedure). For the two participants receiving "enhanced" (90 watt) LIFU, VAS craving ratings revealed active LIFU attenuated craving for participants' primary substances of choice relative to sham sonication. For these participants, reductions were also noted in daily VAS craving ratings (0 = no craving; 10 = most craving ever) across the week following LIFU relative to pre-LIFU (Participant #3 pre-vs post-LIFU: opioids (3.6±0.6 vs 1.9±0.4), heroin (4.2±0.8 vs 1.9±0.4), methamphetamine (3.2±0.4 vs 0.0±0.0), cocaine (2.4±0.6 vs 0.0±0.0), benzodiazepines (2.8±0.5 vs 0.0±0.0), alcohol (6.0±0.7 vs 2.7±0.8), and nicotine (5.6±1.5 vs 3.1±0.7); Participant #4: alcohol (3.5±1.3 vs 0.0±0.0) and nicotine (5.0±1.8 vs 1.2±0.8) (all p's <0.05). Furthermore, relative to screening, longitudinal reductions in cueinduced craving for several substances persisted during the 90-day post-LIFU follow-up evaluation for all participants. In conclusion, LIFU targeting the NAc was safe and acutely reduced substance craving during the LIFU procedure, and potentially had longer-term impact on craving reductions. While early observations are promising, NAc LIFU requires further investigation in a controlled trial to assess the impact on substance craving and ultimately substance use and relapse.